2020
DOI: 10.1186/s13059-020-01992-7
|View full text |Cite
|
Sign up to set email alerts
|

TADsplimer reveals splits and mergers of topologically associating domains for epigenetic regulation of transcription

Abstract: We present TADsplimer, the first computational tool to systematically detect topologically associating domain (TAD) splits and mergers across the genome between Hi-C samples. TADsplimer recaptures splits and mergers of TADs with high accuracy in simulation analyses and defines hundreds of TAD splits and mergers between pairs of different cell types, such as endothelial cells and fibroblasts. Our work reveals a key role for TAD remodeling in epigenetic regulation of transcription and delivers the first tool for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Compared with TADsplimer which specifically identifies split and merge TADs 25 , DiffDomain identifies similar numbers of split and merge TADs between multiple pairs of human cell lines (Supplementary Fig. 8) .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with TADsplimer which specifically identifies split and merge TADs 25 , DiffDomain identifies similar numbers of split and merge TADs between multiple pairs of human cell lines (Supplementary Fig. 8) .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with TADsplimer which specifically identifies split and merge TADs [25], DiffDomain identifies similar numbers of split and merge TADs between multiple pairs of human cell lines (Supplementary Fig. S7).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of current methods call a reorganized TAD if at lesast one of its two boundaries changed between two conditions [11,12,[23][24][25][26][27][28]. These methods enable easy integration with other analysis piplines and identified reorganized TADs have clear biological interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a global flapping of A and B compartments played an important role in T cell lineage specification and in the process of cardiogenesis ( 38 , 45 ). Most TAD boundaries tend to remain stable across cell types, whereas a small subset of TAD boundaries could be cell type specific ( 10 , 44 , 46 ). Disruption of TAD boundary was reported to rewire gene-enhancer interactions and lead to distinct human limb malformations ( 47 ).…”
Section: Discussionmentioning
confidence: 99%